Mesenchymal stem cells in the bone marrow microenvironment: a double-edged sword for AML - Mohamed J. Saadh; Nima Torabi Fard; Ahmed Hussein; Amirhossein Mirzazadeh; Mohammad Siavashi; Fatemeh SeyedMoharami; Shekoofeh Noroozi; Hamed Soleimani Samarkhazan (Journal of Cancer Research and Clinical Oncology)
Abstract Mesenchymal stem cells (MSCs) play a pivotal role in supporting acute myeloid leukemia (AML) cell survival, proliferation, and drug resistance through various mechanisms, including the release of soluble factors, direct cell-cell interactions, and the creation of a leukemia-supportive niche. Conversely, MSCs also demonstrate potential inhibitory effects on AML, including the induction of apoptosis, cell cycle arrest, and the modulation of immune responses. These contrasting effects highlight the complexities of MSC-AML interactions and emphasize the need for further research to understand their therapeutic potential fully. Targeting MSCs represents a promising avenue for AML treatment. Strategies aimed at modifying MSC-mediated support of AML cells, such as inhibiting pro-survival signaling pathways, disrupting the leukemia-supportive niche, and enhancing the immune-stimulatory functions of MSCs, could offer novel therapeutic approaches. However, it is essential to acknowledge the limitations of current research. Further investigations are necessary to elucidate the precise mechanisms underlying the dual effects of MSCs in AML, to identify biomarkers that predict patient response to MSC-targeted therapies, and to develop strategies to overcome potential challenges associated with MSC-based interventions. In conclusion, understanding the multifaceted role of MSCs in AML pathogenesis is crucial for developing innovative therapeutic approaches. By harnessing the potential of MSCs and targeting their interactions with AML cells, we can explore novel strategies to improve treatment outcomes and enhance the overall management of this challenging hematological malignancy. This review underscores the intricate relationship between MSCs and AML within the bone marrow microenvironment.